(untitled) (Nordic Journal of African Studies, 2009)
This paper investigates meaning generation at the explicit level in Chimamanda Ngozi Adichie’s Purple Hibiscus, given that no context-driven study of the text has been attempted. It specifically explores the processes by which the meanings of utterances are modified in use, exemplifying with twenty five percent of transactions in the novel. The study routes its findings through the more recent relevance-theoretical perspective as well as insights from relevant pragmatic models of context, and reveals that the recovery of explicatures involves reference assignment, bridging, gap-filling, disambiguation, and embedding propositional contents of expressions into higher level explicatures. It further demonstrates that these processes facilitate access to the author’s thematic foci, character exposition, location of settings, and cohesive unity. Ultimately, the paper concludes that a study of explicature in Purple Hibiscus assists greatly in understanding conversations in the text, and also aids access to the intended meaning of the author vis-à-vis the overall interpretation of the text.